Preparation of a Sunitinib loaded microemulsion for ocular delivery and evaluation for the treatment of corneal neovascularization in vitro and in vivo - Shi, Jieran; Yang, Jingjing; Xu, Haohang; Luo, Qing; Sun, Jun; Zhang, Yali; Liang, Zhen; Zhao, Ningmin; Zhang, Junjie (Frontiers in Pharmacology, 2023)
Background: Corneal neovascularization (CNV) is a pathological condition that can disrupt corneal transparency, thus harming visual acuity. However, there is no effective drug to treat CNV. Sunitinib (STB), a small-molecule multiple receptor tyrosine kinase inhibitor, was shown to have an effect on CNV. The purpose of this study was to develop an STB microemulsion (STB-ME) eye drop to inhibit CNV by topical application.We successfully prepared an STB-ME by the phase inversion emulsification method, and the physicochemical properties of STB-MEs were investigated. The short-term storage stability, cytotoxicity to human corneal epithelial cells, drug release, ocular irritation, ocular pharmacokinetics and the inhibitory effect on CNV were evaluated in vitro and in vivo.The optimal formulation of STB-ME is composed of oleic acid, CRH 40, Transcutol P, water and sodium hyaluronate (SH). It is a uniform spherical particle with a mean droplet size of 18.74 ± 0.09 nm and a polydispersity index of 0.196 ± 0.004. In the in vitro drug release results, STB-ME showed sustained release and was best fitted by a Korsmeyer-Peppas model (R 2 = 0.9960). The results of the ocular pharmacokinetics in rabbits showed that the formulation containing SH increased the bioavailability in the cornea (2.47-fold) and conjunctiva (2.14-fold). STB-ME (0.05% and 0.1%), administered topically, suppressed alkali burn-induced CNV in mice more effectively than saline, and high-dose (0.1%) STB-ME had similar efficacy to dexamethasone (0.025%).This study provides a promising formulation of STB-ME for the inhibition of CNV by topical administration, which has the excellent characteristics of effectiveness, sustained release and high ocular bioavailability.